Increases in vegetation cover increase response more to climate change than to human activities in the Baiyangdian watershed - Jiashan Gao; Jianying Yang (Environmental Research Communications)
Baiyangdian watershed is located in the upstream of Xiongan New Area, and as an important ecological source of the new area, its vegetation cover status has an important impact on the environmental quality and ecological health of the new area. By analysing the spatial and temporal characteristics of vegetation cover in the Baiyangdian watershed, we investigated the response of climate change and human activities to vegetation cover, and revealed the evolution patterns and driving mechanisms of vegetation cover under changing environments. Utilizing the Google Earth Engine (GEE) and Landsat remote sensing images, the normalized difference vegetation index (NDVI) of the Baiyangdian watershed from 1992 to 2022 was extracted. The temporal and spatial characteristics of vegetation cover were determined using Theil-Sen Median and Mann-Kendall analysis, while factors influencing the spatiotemporal changes in vegetation cover in Baiyangdian were explored through correlation and residual analyses reveal the following: (1) Vegetation cover in the study area showed an increasing trend over time, with a spatial increase from northwest to southeast, revealing the recovery of the ecological environment; (2) Vegetation cover was positively correlated with precipitation and temperature, and the effect of temperature on Baiyangdian was greater than that of precipitation; (3) Residual analyses showed that human activities and climate change had an increasing role in contributing to vegetation cover, and that the dominant factor had changed from human activities to climate changes. The residual analysis shows that human activities and climate change are increasing the vegetation cover, and the dominant factor is changing from human activities to climate change. This study provides a scientific basis for the ecological management of Baiyangdian and the construction of forestry engineering.